Transcriptomic analysis of the inhibition mechanisms against Pseudomonas plecoglossicida by antibacterial aptamer B4 - Tan, Ying; Lin, Xiaojun; Huang, Lixing; Yan, Qingpi; Wang, Jiaen; Weng, Qibiao; Zhengzhang, Yuwei; Chen, Yiran; Ma, Ying; Zheng, Jiang (Frontiers in Veterinary Science, 2024)
Pseudomonas plecoglossicida is a common bacterial pathogen in aquaculture, often leading to visceral white spot disease in large yellow croakers (Pseudosciaena crocea). Previous studies have found that certain aptamers show an efficient antibacterial effect against this pathogen. In this study, we analyzed the transcriptome of P. plecoglossicida to get insights into the antibacterial and inhibitions mechanisms following exposure to the aptamer B4. The results showed seven differentially expressed genes (DEGs) associated with the antibacterial effect of the aptamer, namely sad gene encoding aldehyde dehydrogenase, the paaB gene of phenylacetyl coenzyme A cyclooxygenase, the metN1 gene of ABC transporter proteins, two transposase genes with different positions but identical sequences involved in cutting and splicing DNA sequences, and two hypothetical protein genes with unknown functions. Gene Ontology (GO) analysis showed that the DEGs were mainly involved in DNA-mediated translocation, phenylacetic acid catabolism, growth hormone catabolism, polyamine transporter ATPase activity, betaine aldehyde dehydrogenase activity, ABC transporter protein complex, and other related pathways. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the metabolic pathway of niacin and niacinamide mediated through the sad gene was the most significant and relevant, followed by the metabolism of phenylalanine, alanine, aspartic acid and glutamic acid. Real-time quantitative PCR validation showed that the changes in the DEGs were consistent with the transcriptome analysis. These results suggest that the antibacterial aptamer B4 may inhibit P. plecoglossicida by blocking the synthesis of essential nucleic acids and proteins through the modulation of these DEGs and inhibiting their metabolic pathways.